2015
DOI: 10.1128/iai.03067-14
|View full text |Cite|
|
Sign up to set email alerts
|

Immunoprofiling of the Tryptophan-Rich Antigen Family in Plasmodium vivax

Abstract: h Tryptophan-rich antigens (TRAgs) are an antigen family that has been identified in human and rodent malaria parasites. TRAgs have been proposed as candidate antigens for potential vaccines. The Plasmodium vivax TRAg (PvTRAg) family includes 36 members. Each PvTRAg contains a tryptophan-rich (TR) domain in the C-terminal region. In this study, we recombinantly expressed all 36 PvTRAgs using a cell-free expression system, and, for the first time, profiled the IgG antibody responses against all PvTRAgs in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 38 publications
2
34
0
Order By: Relevance
“…The discrepancy in overall NI values for ape versus human P. vivax strains indicates that MK tests are likely to produce different results depending on which P. vivax strains are used. For the chimpanzee P. vivax strains, only two genes yielded significant results after correction for multiple testing ( P < 0.05), both with NI <1 indicating a significant excess of fixed, potentially adaptive, nonsynonymous differences: one was found to be orthologous to PVP01_1201800, which is an immunogenic member of the tryptophan-rich antigen family of P. vivax ( 27 , 28 ), and the other (orthologous to PVP01_1406200) encodes a conserved Plasmodium protein of unknown function. For the human P. vivax strains, five genes yielded significant MK test results, but all with NI >1, indicating an excess of nonsynonymous polymorphisms ( Dataset S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The discrepancy in overall NI values for ape versus human P. vivax strains indicates that MK tests are likely to produce different results depending on which P. vivax strains are used. For the chimpanzee P. vivax strains, only two genes yielded significant results after correction for multiple testing ( P < 0.05), both with NI <1 indicating a significant excess of fixed, potentially adaptive, nonsynonymous differences: one was found to be orthologous to PVP01_1201800, which is an immunogenic member of the tryptophan-rich antigen family of P. vivax ( 27 , 28 ), and the other (orthologous to PVP01_1406200) encodes a conserved Plasmodium protein of unknown function. For the human P. vivax strains, five genes yielded significant MK test results, but all with NI >1, indicating an excess of nonsynonymous polymorphisms ( Dataset S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, antibodies to anti- P . vivax tryptophan-rich antigen persisted stably for 5 to 12 years in Chinese residents who lived in low malaria-endemic areas [ 25 ]. Recently, P .…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed a very high seropositivity rate amongst the P. vivax patients, indicating that the antigen generates significant humoral immune response . Alternatively, a recent study revealed mean seropositive rate of 60.3% for 36 recombinantly expressed PvTRAgs when antibody responses were measured in the sera from 96 vivax malaria patients and 40 healthy individuals using protein microarray technology . These factors need to be exploited further to test its value as a serodiagnostic marker for vivax malaria.…”
Section: Resultsmentioning
confidence: 99%